Analysis of the Impact Measurement on RE Development in the Context of Artificial Intelligence. (30th July 2022) - Sui, Xiang
Abstract : The research and application of artificial intelligence (AI) have changed the way people live and produce. This paper discusses the factors affecting the development of RE in the context of artificial intelligence, analyzes the industrial status of 31 provincial administrative regions in China from the three dimensions of industrial influence, industrial relevance, and industrial efficiency, and uses gray correlation analysis to evaluate the system and measure.